APPLICATION LEAST SQUARE METHOD TO PREDICT SALES VOLUME IN COMPUTER APPLICATIONS - Lily Utama; Sahni Damerianta Purba., SKom, MMSi (Jurnal Sistem Informasi, 2000)
Scientific writing is intended to simplify decision-makers in predicting the volume of sales, bymaking a computer program to facilitate the calculations so that results would be expected to bemore quickly and accurately. Another aim to be able to see the opportunities that exist incompanies that can take into account the condition of the company to be able to develop moreadvanced again.The result is that the intelligence of elected experience and a good theory will provide the basicsis best to conduct the sales forecast. Forecasting by using the least square method using theassumption that what happens in the future no matter what happened in the past, state variablesmust be fixed for future